Q: Applying PEMDAS, simplify these expressions
6 + 4(3^2) – 20

A: 6 + 4(3^2) – 20 = 6 + 4(9) - 20 = 6 + 36 - 20 = 42 - 20 = 22

Question

Asked 3/22/2012 7:45:42 PM

Updated 7/16/2014 11:42:01 AM

1 Answer/Comment

Edited by andrewpallarca [7/16/2014 11:41:11 AM]

Rating

3

6 + 4(3^2) – 20

= 6 + 4(9) - 20

= 6 + 36 - 20

= 42 - 20

= 22

= 6 + 4(9) - 20

= 6 + 36 - 20

= 42 - 20

= 22

Added 7/16/2014 11:42:01 AM

This answer has been confirmed as correct and helpful.

Simplify by Combining Like Terms:
1) x – 5x + 12x
**Weegy:**
x – 5x + 12x
= -4x + 12x
= 8x
(More)

Question

Not Answered

Updated 8/16/2014 3:50:12 PM

0 Answers/Comments

x – 5x + 12x
**Weegy:** 1.5x + 1.2 = 5.7; 1.5x =4.5; x = 4.5/1.5; x=3 **User:** implify by Combining Like Terms:
1) x – 5x + 12x
2) 14xy3 – 22xy3 + 5xy3
Simplify by using the Distributive Property
3) 4a + 5(b – 2)
4) 8(3a + 2b – 5c)
Applying PEMDAS, simplify these expressions
5) 6 + 4(32) – 20
6) 9 + 4 (10 ÷ 2 ) – 6
7) -12 – 48 ÷ 6 x 32 + 10
Simplify the espressions with grouping symbols
8) 14 – [ 3 + (8 – 2)]
Evaluate the expressions
9) Given 4x – 12, evaluate when x = -7
10) Given 3x2 + 2x – y, evaluate when x = -3 and y = 9
**Weegy:** x = -7/5 (More)

Question

Expert Answered

Updated 3/29/2014 10:01:21 AM

1 Answer/Comment

27,006,851 questions answered

There are no comments.